Sexual dimorphism in the horn size of a pair-forming coral reef butterflyfish - Shiratsuchi, Satoshi (PLoS One, 2020)
Sexual dimorphism is a common in the animal kingdom and is often linked to mate choice or competition for mates in polygynous mating systems. However, sexual dimorphism is less common in species that form heterosexual pairs and has not been recorded in pair-forming coral-reef fish. Here we demonstrate a pronounced morphological difference between males and females in the humphead bannerfish (Heniochus varius)—a pair-forming coral reef butterflyfish. Males of paired individuals collected in Kimbe Bay, Papua New Guinea had substantially larger hump and horn protrusions on their heads than females. Fish were also sexed, sized and aged to determine the reproductive and demographic basis of the pairing behaviour. H. varius pairs were exclusively heterosexual and were assorted strongly by total length and slightly less so by age. Females in pairs were generally the same size as male partners, but were frequently older by a year and sometimes more. Hump and horn lengths increased proportionally to body-size in both sexes, with horns growing at a greater rate among males. These findings suggest that H. varius form pairs primarily for reproductive purposes, with selection via a size-assortative process that likely also extends to selection for larger hump and horn protrusions among males. The larger humps and horns in males appear to be the first recorded example of a secondary sexual morphological characteristic in a pair-forming coral reef fish species.